Irregular colorings of friendship graph families. (18th May 2020) - Rohini, A.; Venkatachalam, M.
Abstract: In this paper, we acquired the irregular chromatic number for the following graphs: M ( fn ), T ( fn ), C ( fn ), L ( fn ), M ( DFn ), T ( DFn ), L ( DFn ), C ( DFn ), M ( SFn ), T ( SFn ), L ( SFn ), C ( SFn ).